Ambiguity and confusion around the celebration of the Mawlid. - Mehdi Berriah (Revue des Mondes Musulmans et de la Méditerranée)
As the supposed date of the birth of Prophet Muḥammad approaches, the debate within the Muslim community about the legality or permissibility of celebrating the birth of the Prophet (Mawlid) of Islam opens up each year: condemnable bidʿa (innovation) to some since neither the Prophet nor his Companions celebrated it during their lifetime ; Bidʿa ḥasana (good innovation) for others who see this event as an opportunity to show respect and love for the Prophet by recalling traditions (sunan) and certain episodes of his life. In addition to the Sunna, both sides of this contemporary debate draw on medieval authors who discussed the issue of celebrating al-mawlid al-nabawī in their time. Among these scholars, Ibn Taymiyya (d. 728/1328), one of the most divisive and influential medieval theologians in contemporary Islamic thought, seems to be a particular case. Indeed, his writings are cited by both supporters and opponents of the Mawlid to give more weight to their speeches. The use of the same source to support antagonistic positions ultimately leads to confusion as to the real position of Ibn Taymiyya on the issue, as he is sometimes presented as a supporter of the Mawlid while elsewhere as a fierce opponent. The aim of this article is twofold. The first is to analyse the reception of Ibn Taymiyya’s words on the subject and how they are used and integrated into the discourse of contemporary religious actors involved in the debate on the Mawlid. The second aim is to use the comparison of sources to clarify Ibn Taymiyya’s stance on the Mawlid, a topic that is unquestionably relevant in ongoing debates within the Muslim religious community.